The effect of cooling media and quenching temperature on the tempering process of AISI 1045 steel. - Saputro, Akbar Dicky; Listyanda, R. Faiz; Darmo, Aditya Noor Setyo Hadi; Mulyaningsih, Nani (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2026)
AISI 1045 steel is widely used in machine components due to its high strength and good wear resistance, but its mechanical properties can still be optimized through heat treatment. This research aims to determine the effect of cooling media and variations in tempering temperature on the characteristics of AISI 1045 steel. The problem studied is how the quenching temperature (800°C and 850°C) and the type of cooling media (25% salt water and biodiesel) influence the tensile strength, hardness, and microstructure of the steel. The research method was carried out experimentally with quenching and tempering heat treatment at a temperature of 550°C for 60 minutes, followed by tensile tests, Vickers hardness tests, and microstructure observations. The research results showed that the highest hardness value was found in the 850°C quenched salt water specimen, which was 576.10 kgf/μm, while the highest tensile strength in the tempered 850°C salt water specimen was 1047.53 MPa, and the highest strain in the tempered 850°C biodiesel specimen was 29.17%. The formed microstructure shows the presence of tempered martensite and fine carbide precipitation, which increases the material’s ductility. In conclusion, the combination of a quenching temperature of 850°C with salt water media.